An Optimization Framework for Job Rotation to Better Assess the Impact on Overall Risk. (September 2018) - Vinel, Alexander; Mehdizadeh, Amir; Schall, Mark C.; Gallagher, Sean; Sesek, Richard F.
We aim to study the potential of job rotation schemes to improve worker safety. To this end, we developed a novel optimization framework based on a recently proposed fatigue-failure model for musculoskeletal disorder (MSD) risk evaluation. We then employed it to conduct an illustrative case study. We demonstrate that the effect of job rotation is highly dependent on the composition of the job pool. Namely, if the job pool contains high-risk tasks (e.g., those carrying greater than 90% probability of developing a disorder), then it may be impossible to observe any risk improvement with rotations alone. On the other hand, if all jobs are already relatively low-risk, then a rotation may be very helpful in achieving risk equity.